Sub-regional conflicts and selective autonomy in J&K: Hill Councils in power. (October 2014) - Wani, Gull
The State of Jammu and Kashmir (J&K) is examined here in terms of its unique history, geography and cross-cultural composition. Its three regions are not just historically and culturally distinct but each have sub-regions and religious minorities with their own claims to autonomy and devolved power. The author examines the diversity of Jammu, Kashmir and Ladakh and assesses, from a personal study tour, the successes and failures of Hill Councils that have been established in Leh and Kargil (Ladakh) and the prospect of creating others in the Jammu region. Sub-regionalism becomes a potent force in the absence of strong regional consciousness, he argues. Regionalism in general is a product of India's diversity; sub-regionalism the result of geographic, historical and socio-economic factors – J&K is a case in point.